Historical dictionary of Syria - Commins, David Dean; Lesch, David W (Historical dictionaries of Asia, Oceania, and the Middle East, 2014)
This third edition covers the recent events in Syria and the history that led up to these events through a chronology, an introductory essay, and an extensive bibliography. The cross-referenced dictionary section has more than 500 entries on significant people, places, events, political parties, institutions, literature, music, and arts